2020
DOI: 10.3389/fimmu.2020.609948
|View full text |Cite
|
Sign up to set email alerts
|

MIF-Dependent Control of Tumor Immunity

Abstract: Initially identified as a T lymphocyte-elicited inhibitor of macrophage motility, macrophage migration inhibitory factor (MIF) has since been found to be expressed by nearly every immune cell type examined and overexpressed in most solid and hematogenous malignant cancers. It is localized to both extracellular and intracellular compartments and physically interacts with more than a dozen different cell surface and intracellular proteins. Although classically associated with and characterized as a mediator of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 197 publications
(207 reference statements)
2
76
2
Order By: Relevance
“…These findings suggested that serum MIF appeared to be an important biological indicator for reflecting disease severity and an independent predictor to detect those who might best benefit from SLIT. MIF is a unique pleiotropic protein which is mainly expressed on monocytes, macrophages, and lymphocytes, and serves as an important pro-inflammatory mediator and immune regulator that participates in innate and adaptive immune responses (Noe and Mitchell, 2020;Liu et al, 2021). Prior publications reported a pivotal role of MIF in the pathogenesis of type 2-mediated inflammation, especially in allergic and autoimmune diseases (Yoshihisa et al, 2011;de Souza et al, 2015;Bozza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that serum MIF appeared to be an important biological indicator for reflecting disease severity and an independent predictor to detect those who might best benefit from SLIT. MIF is a unique pleiotropic protein which is mainly expressed on monocytes, macrophages, and lymphocytes, and serves as an important pro-inflammatory mediator and immune regulator that participates in innate and adaptive immune responses (Noe and Mitchell, 2020;Liu et al, 2021). Prior publications reported a pivotal role of MIF in the pathogenesis of type 2-mediated inflammation, especially in allergic and autoimmune diseases (Yoshihisa et al, 2011;de Souza et al, 2015;Bozza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…MIF affects both tumor progression and tumor-associated immune responses. It is becoming increasingly evident that MIF plays an important regulatory role in governing TAM-dependent tumor initiation, progression, and metastatic disease phenotypes, although a unifying mechanism that explains how MIF contributes to this seemingly divergent M1 and M2 macrophage phenotypes is still lacking [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of MIF to CD74 in melanoma cells promotes PI3K/AKT activation and cell survival. We detected elevated expression of a second MIF receptor, CXCR4, and of another cognate ligand, CXCL12, in the bTIL region; CXCR4 activation leads to expansion of immunosuppressive Tregs (Noe and Mitchell, 2020). CXCR4 is the chemokine receptor most commonly found on cancer cells, and binding to CXLC12 is thought to promote invasive and migratory phenotypes leading to metastasis (Sun et al, 2010).…”
Section: Single-cell Analysis Of Invasive Tumor Reveals Large Scale Gradients In Lineage Immune and Proliferation Markersmentioning
confidence: 98%